1998
DOI: 10.1254/jjp.76.199
|View full text |Cite
|
Sign up to set email alerts
|

Effects of KW-5617 (Zaldaride Maleate), a Potent and Selective Calmodulin Inhibitor, on Secretory Diarrhea and on Gastrointestinal Propulsion in Rats

Abstract: KW-5617 (zaldaride maleate), 1,3-dihydro-1-[1-[(4-methyl-4H,6H-pyrrolo[1,2-a][4,1]-benzoxazepin -4-yl)methyl]-4-piperidinyl]-2H-benzimidazol-2-one maleate, is a selective calmodulin inhibitor. We studied the effects of KW-5617 on secretory diarrhea and gastrointestinal propulsion in rats, as compared with those of loperamide, a conventional anti-diarrheal drug. Diarrhea was induced in rats either by 16,16-dimethyl prostaglandin E2 (500 microg/kg, i.p.) or by castor oil (1 ml/100 g body weight, p.o.). In the 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…Loperamide inhibited diarrhea caused by various agents and also the stool output stimulated by WRS in the present study, as previously reported (24,25). In our study, effective doses of loperamide were very variable with a 100 times difference between the different diarrhea models.…”
Section: Discussionsupporting
confidence: 90%
“…Loperamide inhibited diarrhea caused by various agents and also the stool output stimulated by WRS in the present study, as previously reported (24,25). In our study, effective doses of loperamide were very variable with a 100 times difference between the different diarrhea models.…”
Section: Discussionsupporting
confidence: 90%
“…While intestinal or hepatic lipid accumulation has not been explored in cholera, host MsrA and its interaction with luminal MetO may play a role in the osmotic diarrhea of this disease. Calmodulin is a well-established facilitator of secretory diarrhea, and calmodulin antagonists have been developed as anti-diarrheal treatments [43, 44]. This is true, in particular, for cholera, whose secretory diarrhea depends on the CFTR chloride and SK potassium channels, both of which are calmodulin-dependent [45, 46].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, NOS1-deficient mice have been shown to have reduced gastric emptying (31). In contrast, the major action of loperamide is to reduce intestinal transit, rather than gastric emptying (32,33). Nevertheless, although loperamide is primarily an agonist of -opioid receptors, it can also block Ca 2ϩ channels and inhibit calmodulin-mediated effects in neurons (28).…”
Section: Discussionmentioning
confidence: 99%